Sodium ferrimanganate layered positive electrode material as well as preparation method and application of molten salt of sodium ferrimanganate layered positive electrode material

By combining molten salt method and solid phase reaction method in sodium ion battery positive electrode material, Na0.67Mn0.5Fe0.5O2 positive electrode material was synthesized, which solved the problems of poor cycle life and low energy density, and achieved higher first-time discharge specific capacity and cycle stability.

CN119812253AActive Publication Date: 2025-04-11XIAN TECH UNIV

Patent Information

Application Number
CN202411920965.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-11
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The poor cycle life and low energy density of the positive electrode material of sodium ion battery limit their application in the fields of energy storage and power.

Method used

The molten salt method and solid phase reaction method were used to synthesize Na0.67Mn0.5Fe0.5O2 positive electrode material by combining potassium chloride as molten salt to improve the grain dispersion and morphological uniformity of the material.

Benefits of technology

The first discharge specific capacity and cycle stability of the positive electrode material of sodium ion battery are significantly improved, and the energy density and cycle performance of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812253A_ABST
    Figure CN119812253A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion batteries, in particular to a preparation method and application of a sodium ferrimanganate layered positive electrode material and fused salt. The preparation method comprises the following steps: weighing a sodium source, a manganese source, an iron source and potassium chloride molten salt according to a stoichiometric ratio, adding absolute ethyl alcohol, carrying out ball milling and mixing to obtain a precursor, pressing dried precursor powder, calcining, grinding the calcined material into fine powder, carrying out suction filtration and washing with deionized water and absolute ethyl alcohol, and drying to obtain a precursor powder; and carrying out annealing treatment to obtain the sodium ferrimanganate layered positive electrode material. The first discharge capacity of the positive electrode material prepared by using a molten salt method at 0.1 C is up to 214 mAh / g, the discharge capacity at 1C rate is 175 mAh / g, and the discharge capacity retention rate after 100 cycles is 64.91%; the preparation method is simple, has high safety, is suitable for large-scale industrial production, and can be widely applied to the field of sodium ion battery layered positive electrodes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ferromanganate layered positive electrode material and a preparation method and application of its molten salt. Background Art

[0002] Globally, due to the continuous consumption of fossil energy and the severe environmental problems that come with it, the use of green energy to generate electricity is becoming more and more popular. However, due to its geographical and time limitations, energy storage equipment is needed to store it. Secondary batteries are widely used because of their stable storage, safety and efficiency. Among them, the most representative lithium-ion battery has been widely used in 3C electronics and power vehicles due to its high energy density and long cycle life. However, the development of lithium-ion batteries is limited by poor cycle stability, poor rate performance, and narrow operating temperature range. In addition, the price of lithium ore has continued to rise in recent years, and lithium resources are unevenly distributed around the world, which has hindered the further development of lithium-ion batteries. Therefore, sodium, which is abundant in the earth's crust and is also the first main group in the periodic table, has once again attracted the attention of scientific researchers since it was first proposed in the 1970s.

[0003] Sodium-ion batteries have the advantages of low cost, abundant raw materials, good safety, and good performance at high and low temperatures. They have great development potential and broad market prospects in the fields of energy storage and power. However, the positive electrode materials of sodium-ion batteries also face two key problems that need to be solved urgently: poor cycle life and low energy density.

[0004] The molten salt method is usually used as a method for preparing positive electrode materials. It provides a molten liquid environment under high temperature conditions, so that the grain growth is transformed from a simple single-phase mechanism to a two-phase mechanism, reducing the energy required in the mass transfer process. At the same time, due to the dissolution recrystallization mechanism, the primary particles in the precursor are rarely aggregated together, and it is easier to form a regular, uniform and good grain morphology, which is beneficial to the improvement of the electrochemical performance of the positive electrode material. The existing molten salt method is generally used for the preparation of positive electrode materials for ternary lithium-ion batteries, and the grain morphology of the positive electrode materials for ternary lithium-ion batteries is regulated. The selected molten salt generally uses lithium salts with a lower melting point, such as LiOH, LiSO4, etc. In the file with application number "CN202410127517.0", "A type O3 nickel-iron-manganese-based sodium positive electrode material and its preparation method" is provided. The method prepares the positive electrode material of the sodium ion battery by pre-sintering and secondary sintering. The problem is that the material prepared by the traditional pre-sintering and secondary sintering method has a low first discharge specific capacity and unsatisfactory electrochemical performance. Summary of the invention

[0005] The purpose of the present invention is to provide a sodium ferromanganate layered positive electrode material for sodium ion batteries and a preparation method and application of its molten salt, which improves the sodium ferromanganate layered positive electrode material Na prepared by the traditional method. 0.67 Mn 0.5 Fe 0.5 Poor O2 grain morphology leads to low first discharge specific capacity and poor cycle stability.

[0006] In order to achieve the purpose of the present invention, the technical solution provided by the present invention is: a molten salt preparation method of sodium ferromanganate layered positive electrode material, comprising the following steps:

[0007] Step 1: weigh the sodium source, manganese source and iron source according to the stoichiometric ratio, and then add a certain amount of potassium chloride as molten salt, the amount of potassium chloride added is x:1 with the atomic ratio of the added sodium, wherein the value range of x is 0.5≤x≤5;

[0008] Step 2: Add an appropriate amount of anhydrous ethanol to the weighed powder, mix well by wet grinding with a planetary ball mill, and then transfer to a blast oven to dry overnight;

[0009] Step 3: After drying, the mixture is pressed by a tablet press and sintered at high temperature to obtain a positive electrode material of sodium ferromanganate mixed with KCl molten salt.

[0010] Step 4: Grind into fine powder and filter and wash with deionized water and anhydrous ethanol. After filtering, put the sample into a blast oven for drying;

[0011] Step 5: The washed powder is filtered and subjected to secondary calcination and annealing treatment to obtain a sodium ferromanganate layered positive electrode material.

[0012] Furthermore, in the above step 1, the sodium source is one or more of sodium carbonate, anhydrous sodium acetate, and sodium sulfate, the manganese source is manganese dioxide or manganese acetate tetrahydrate, and the iron source is ferric oxide.

[0013] Furthermore, in the above step 2, the rotation speed of the planetary ball mill for ball milling is 400-600 rpm, and the ball milling time is 6-8 h.

[0014] Furthermore, in the above step three, the pressing pressure is 10-12MPa, the high temperature sintering temperature is 900-1000°C, the starting temperature is room temperature, the temperature is increased by 3-5°C per minute, and the temperature is kept for 10-20 hours. After the insulation is completed, the sample is naturally cooled to room temperature with the furnace, and the heat treatment is carried out in air throughout the process.

[0015] Furthermore, in the above step 5, the annealing temperature is 500-700° C. and the time is 5-10 hours.

[0016] Furthermore, in the above step 4, an organic filter membrane is used for vacuum filtration, and deionized water is first used for repeated filtration 3-5 times to fully remove the residual potassium chloride molten salt, and then anhydrous ethanol is used for repeated filtration 3-5 times.

[0017] Furthermore, in the above steps 2 and 4, the temperature of the blast oven is 60-80° C., and the drying time is 10-12 hours.

[0018] Furthermore, a sodium ferromanganate layered positive electrode material is prepared by the above molten salt preparation method.

[0019] Furthermore, the sodium ferromanganate sodium ion positive electrode material prepared by the above molten salt preparation method is used in the field of sodium ion batteries.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The present invention combines the molten salt method and the solid phase reaction method for the first time to synthesize Na 0.67 Mn 0.5 Fe 0.5 O2 positive electrode material improves the dispersibility of the positive electrode material particles of the sodium ion battery, and the selected KCl molten salt is low in cost, and the potassium ion radius in the molten state is large, and it is not easy to embed into the sodium ion layer, which has little impact on the positive electrode material of the sodium ion battery. The presence of molten salt provides a molten liquid environment for the precursor under high temperature conditions, so that the grain growth changes from a single-phase mechanism to a two-phase mechanism, reducing the energy required in the mass transfer process. At the same time, due to the dissolution recrystallization mechanism, the primary particles in the precursor rarely aggregate together, making it easier to form a good grain morphology, reducing the residual alkali on the surface, and ultimately improving the first discharge specific capacity and cycle stability of the sodium ion battery positive electrode material. Na synthesized by molten salt method and high temperature solid phase reaction method 0.67 Mn 0.5 Fe 0.5 Taking O2 positive electrode material as an example, in the voltage window of 1.5-4.3V and the charge and discharge rate of 0.1C, the first discharge capacity of the material without using KCl as molten salt is 178mAh / g, and the Na prepared by molten salt method is 178mAh / g. 0.67 Mn 0.5 Fe 0.5 The first discharge capacity of the O2 positive electrode material is as high as 214 mAh / g. The first discharge capacity of the material without KCl as molten salt at 1C rate is 133 mAh / g, and the discharge capacity retention rate after 100 cycles is 55.22%. 0.67 Mn 0.5 Fe 0.5 The first discharge capacity of the O2 positive electrode material is 175 mAh / g, and the discharge capacity retention rate after 100 cycles is 64.91%.

[0022] 2. In the preparation method of the present invention: the method of mixing the precursor and the molten salt in one step by mechanical ball milling is simple and easy to synthesize; the molten salt KCl material used is cheap, is not easy to embed into the material lattice during high-temperature calcination, and is easy to separate from the material later, which is suitable for large-scale industrial production;

[0023] 3. The positive electrode material prepared by the present invention can be widely used in the field of layered positive electrodes for sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is the XRD pattern of sodium ferromanganate prepared in Example 1 and the comparative example;

[0025] Figure 2 It is the microscopic morphology of sodium ferromanganate prepared in Example 1 and the comparative example;

[0026] Figure 3 It is a comparison diagram of the charge and discharge curves of the sodium ferromanganate positive electrode material prepared in Example 1 and the comparative example at a rate of 0.1C;

[0027] Figure 4 The cycle performance of the sodium ferromanganate positive electrode material prepared in Example 1 and the comparative example under the charge and discharge rate condition of 1C;

[0028] Figure 5 It is a rate performance diagram of sodium ferromanganate prepared in Example 1 and the comparative example;

[0029] Figure 6 It is the 1C, 100-cycle median voltage diagram of the sodium ferromanganate prepared in Example 1 and the comparative example;

[0030] Figure 7 is the GITT diagram of sodium ferromanganate prepared in Example 1 and the comparative example; DETAILED DESCRIPTION

[0031] The present invention will be described in detail below with reference to the accompanying drawings and embodiments.

[0032] Example 1, a sodium ferromanganate layered positive electrode material and a method for preparing a molten salt thereof, are prepared by the following synthesis method:

[0033] 1) According to the chemical formula Na 0.67 Mn 0.5 Fe 0.5 O2 weighed stoichiometric Na2CO3, MnO2, Fe2O3 and KCl in a 1:1 atomic ratio with Na;

[0034] 2) adding an appropriate amount of anhydrous ethanol, mixing by wet grinding in a planetary ball mill to obtain a precursor, and transferring it to a blast oven to dry overnight; the rotation speed of the planetary ball mill is 600 rpm, the ball milling time is 6 hours, and drying at 80° C. for 10 hours to obtain a mixed powder;

[0035] 3) 1.6 g of the mixture powder was pressed by a tablet press at 12 MPa, and the temperature was raised by 3°C per minute from room temperature, and kept at 950°C for 15 h. After the heat preservation, the sample was naturally cooled to room temperature in the furnace. During the heat treatment, air was continuously blown into the muffle furnace by an air pump to provide sufficient oxygen for the reaction process;

[0036] 4) The calcined powder is ground into fine powder and washed by suction with deionized water and anhydrous ethanol. After the suction filtration, the sample is placed in a blast oven for drying;

[0037] The vacuum filtration uses an organic filter membrane, first repeatedly filter with deionized water for 5 times to fully remove the residual potassium chloride molten salt, and then repeatedly filter with anhydrous ethanol for 3 times to increase the subsequent drying speed and reduce the continuous impact of deionized water on the positive electrode material powder; after washing away the excess KCl molten salt, dry it at 80°C for 10 hours;

[0038] 5) The dried powder was annealed at 600° C. for 5 h to obtain a sodium ferromanganate layered positive electrode material.

[0039] Example 2, a sodium ferromanganate layered positive electrode material and a method for preparing a molten salt thereof, are prepared by the following synthesis method:

[0040] 1) According to the chemical formula Na 0.67 Mn 0.5 Fe 0.5 O2 weighed stoichiometric Na2CO3, MnO2, Fe2O3 and KCl in a 1:1 atomic ratio with Na;

[0041] 2) adding an appropriate amount of anhydrous ethanol, mixing evenly by wet grinding in a planetary ball mill, and then transferring to a blast oven to dry overnight; the rotation speed of the planetary ball mill is 400 rpm, the ball milling time is 8 hours, and drying at 80° C. for 10 hours to obtain a mixed powder;

[0042] 3) 1.6 g of the mixture powder was pressed by a tablet press at 12 MPa, and the temperature was raised by 3°C per minute from room temperature, and kept at 950°C for 15 h. After the heat preservation, the sample was naturally cooled to room temperature in the furnace. During the heat treatment, air was continuously blown into the muffle furnace by an air pump to provide sufficient oxygen for the reaction process;

[0043] 4) The calcined powder is ground into fine powder and washed by suction with deionized water and anhydrous ethanol. After the suction filtration, the sample is placed in a blast oven for drying;

[0044] The vacuum filtration uses an organic filter membrane, first repeatedly filter with deionized water for 3 times to fully remove the residual potassium chloride molten salt, and then repeatedly filter with anhydrous ethanol for 5 times to increase the subsequent drying speed and reduce the continuous impact of deionized water on the positive electrode material powder; after washing away the excess KCl molten salt, dry it at 80°C for 10 hours;

[0045] 5) The dried powder was annealed at 600° C. for 5 h to obtain a sodium ferromanganate layered positive electrode material.

[0046] Example 3, a sodium ferromanganate layered positive electrode material and a method for preparing a molten salt thereof, are prepared by the following synthesis method:

[0047] 1) According to the chemical formula Na 0.67 Mn 0.5 Fe 0.5 O2 weighed stoichiometric Na2CO3, CH3COONa, Na2SO4, MnO2, Fe2O3 (wherein each sodium source provides 1 / 3 of the total sodium) and KCl in a 1:1 atomic ratio with Na;

[0048] 2) adding an appropriate amount of anhydrous ethanol, mixing evenly by wet grinding in a planetary ball mill, and then transferring to a blast oven to dry overnight; the rotation speed of the planetary ball mill is 400 rpm, the ball milling time is 6 hours, and drying at 80° C. for 10 hours to obtain a mixed powder;

[0049] 3) 1.6 g of the mixture powder was pressed by a tablet press at 12 MPa, and then the temperature was raised by 3°C per minute from room temperature and calcined at 950°C for 15 h. After the heat preservation, the sample was naturally cooled to room temperature in the furnace. During the heat treatment, air was continuously blown into the muffle furnace by an air pump to provide sufficient oxygen for the reaction process;

[0050] 4) The calcined powder is ground into fine powder and washed by suction with deionized water and anhydrous ethanol. After the suction filtration, the sample is placed in a blast oven for drying;

[0051] The vacuum filtration uses an organic filter membrane, first repeatedly filter with deionized water for 5 times to fully remove the residual potassium chloride molten salt, and then repeatedly filter with anhydrous ethanol for 5 times to increase the subsequent drying speed and reduce the continuous impact of deionized water on the positive electrode material powder; after washing away the excess KCl molten salt, dry it at 80°C for 10 hours;

[0052] 5) The dried powder was annealed at 600° C. for 5 h to obtain a sodium ferromanganate layered positive electrode material.

[0053] Example 4, a sodium ferromanganate layered positive electrode material and a method for preparing a molten salt thereof, are prepared by the following synthesis method:

[0054] 1) According to the chemical formula Na0.67 Mn 0.5 Fe 0.5 O2 weighed stoichiometric Na2CO3, (CH3COO)2Mn·4H2O, Fe2O3 and KCl in a 1:1 atomic ratio with Na;

[0055] 2) adding an appropriate amount of anhydrous ethanol, mixing evenly by wet grinding in a planetary ball mill, and then transferring to a blast oven to dry overnight; the rotation speed of the planetary ball mill is 600 rpm, the ball milling time is 8 hours, and drying at 60° C. for 12 hours to obtain a mixed powder;

[0056] 3) Take 1.6g of the mixture powder and press it with a tablet press at 10MPa. The temperature is raised by 5°C per minute from room temperature and kept at 950°C for 15h. After the heat preservation, the sample is naturally cooled to room temperature in the furnace. During the whole heat treatment, air is continuously blown into the muffle furnace by an air pump to provide sufficient oxygen for the reaction process.

[0057] 4) The calcined powder is ground into fine powder and washed by suction with deionized water and anhydrous ethanol. After the suction filtration, the sample is placed in a blast oven for drying;

[0058] The vacuum filtration uses an organic filter membrane, first repeatedly filter with deionized water for 3 times to fully remove the residual potassium chloride molten salt, and then repeatedly filter with anhydrous ethanol for 3 times to increase the subsequent drying speed and reduce the continuous impact of deionized water on the positive electrode material powder; after washing away the excess KCl molten salt, dry it at 60°C for 12 hours;

[0059] 5) The dried powder is annealed at 700° C. for 8 h to obtain a sodium ferromanganate layered positive electrode material.

[0060] Comparative Example, Preparation of Na 0.67 Mn 0.5 Fe 0.5 O2 positive electrode material is prepared by the following synthesis method:

[0061] 1) According to the chemical formula Na 0.67 Mn 0.5 Fe 0.5 O2 weighs Na2CO3, MnO2, Fe2O3 in stoichiometric proportion;

[0062] 2) drying the uniformly mixed precursors at 80° C. for 10 hours to obtain a mixed powder;

[0063] 3) The mixture powder is heated from room temperature to 950°C for 15 hours at a temperature of 3°C per minute. After the heat treatment, the sample is naturally cooled to room temperature in the furnace. During the heat treatment, an air pump continuously blows air into the muffle furnace to provide sufficient oxygen for the reaction process.

[0064] In the above examples, sodium carbonate, manganese dioxide, and ferric oxide in Example 1 were added with KCl in a 1:1 atomic ratio of Na to prepare Na 0.67 Mn 0.5 Fe 0.5 O2 positive electrode material has the highest discharge capacity and is the best embodiment.

[0065] The test results are as follows:

[0066] like Figure 1 As shown, the XRD patterns of the comparative example and Example 1 show that the structures of both samples belong to the P2 phase. Compared with the comparative example, the diffraction peak intensity of Example 1 is stronger, indicating that the crystallinity of Example 1 is better. Example 1 absorbs water during storage and produces a peak representing a hydrated phase at a low angle.

[0067] like Figure 2 As shown, the scanning electron microscope images of the comparative example and Example 1 show that the crystal agglomeration phenomenon of Example 1 is rare, the crystal grains are nearly hexagonal sheet structures, and the crystal grain size is above 1 μm. The crystal grain agglomeration phenomenon of the comparative example is serious, many crystal grains are bonded together to form particle communities, the crystal grain shape is irregular, and the size of single small crystal grains is mostly in the range of 500-600nm.

[0068] like Figure 3 As shown, under the voltage window of 1.5-4.3V and the current of 0.1C, the first discharge specific capacities of the comparative example and Example 1 are 178.17mAh / g and 214.03mAh / g, respectively, and the first coulombic efficiencies are 201.51% and 243.00%, respectively. The first discharge capacity and the first coulombic efficiency of Example 1 are both higher than those of the comparative example, because the use of KCl as the molten salt provides a liquid phase melting environment for the growth of grains under a high temperature environment, making the grains under the two-phase mechanism grow more uniformly, and avoiding large-sized agglomeration, thereby improving the first discharge capacity.

[0069] like Figure 4 As shown, after 100 cycles of charge and discharge of Example 1 and the comparative example under a wide voltage window of 1.5-4.3V and a high current of 1C, the discharge specific capacities of the comparative example and Example 1 were 73.52mAh / g and 113.85mAh / g, respectively, and the corresponding capacity retention rates were 55.22% and 64.91%, respectively, which increased by 9.69%. The improvement in capacity retention is due to the more uniform volume change of the positive electrode particles with more uniform grain size under a wide voltage window, resulting in less stress, which greatly inhibits the generation of intergranular cracks and avoids further side reactions between the positive electrode material and the electrolyte.

[0070] like Figure 5It is a rate performance diagram of the comparative example and Example 2 under the wide voltage window of 1.5-4.3V and the currents of 0.1C, 1C, 3C, 5C, 10C and 0.1C, wherein the first discharge specific capacities of the comparative example under the currents of 0.1C, 1C, 3C, 5C, 10C and 0.1C are 170.54mAh / g, 116.88mAh / g, 91.08mAh / g, 78.16mAh / g, 54.18mAh / g and 148.42mAh / g respectively, and the first discharge specific capacities of Example 1 under the currents of 0.1C, 1C, 3C, 5C, 10C and 0.1C are 200.69mAh / g, 158.63mAh / g, 125.46mAh / g, 106.64mAh / g, 77.09mAh / g and 188.95mAh / g. The discharge specific capacities of Example 1 at different rates are increased by 30.15 mAh / g, 41.75 mAh / g, 34.38 mAh / g, 28.48 mAh / g, 22.91 mAh / g and 40.53 mAh / g respectively compared with the comparative example.

[0071] like Figure 6 As shown, the median voltages of the comparative example and the example 1 after 100 cycles at 1C current and 1.5-4.3V voltage are 2.313V and 2.329V, respectively, and the voltage decay per cycle is 2.06mV and 1.15mV. This indicates that the more uniform grain size inhibits the generation of intergranular cracks, stabilizes the layered structure of the material, and hinders further adverse side reactions at the interface between the electrolyte and the particles, thereby inhibiting voltage decay.

[0072] like Figure 7 As shown, the comparative example and Example 1 were activated at 1.5-4.3V, 0.1C for one cycle, and then charged or discharged at 0.1C constant current pulse for 30min, and then relaxed for 2h to reach a GITT curve close to the equilibrium state. The sodium ion diffusion coefficient (D Na+ ) in 10 -6.9 cm 2 S -1 In the range, the sodium ion diffusion coefficient (D Na+ ) in 10 -6.7 cm 2 S -1 The sodium ion diffusion coefficient of the positive electrode material prepared by the molten salt method is larger than that of the positive electrode material not prepared by the molten salt method, and the sodium ion migration kinetics is better.

[0073] It should be understood that the above description is for illustration and not for limitation. By reading the above description, all embodiments and all applications beyond the examples provided will be apparent to those skilled in the art.

Claims

1. A method for preparing a molten salt of a sodium ferromanganate layered positive electrode material, characterized in that: The following steps are involved: Step 1: weigh the sodium source, manganese source and iron source according to the stoichiometric ratio, and then add a certain amount of potassium chloride as molten salt, the amount of potassium chloride added is x:1 with the atomic ratio of the added sodium, wherein the value range of x is 0.5≤x≤5; Step 2: Add an appropriate amount of anhydrous ethanol to the weighed powder, mix well by wet grinding with a planetary ball mill, and then transfer to a blast oven to dry overnight; Step 3: After drying, the mixture is pressed by a tablet press and sintered at high temperature to obtain a positive electrode material of sodium ferromanganate mixed with KCl molten salt. Step 4: Grind into fine powder and filter and wash with deionized water and anhydrous ethanol. After filtering, put the sample into a blast oven for drying; Step 5: The washed powder is filtered and subjected to secondary calcination and annealing treatment to obtain a sodium ferromanganate layered positive electrode material.

2. The method for preparing a molten salt of a sodium ferromanganate layered positive electrode material according to claim 1, characterized in that: In the step 1, the sodium source is one or more of sodium carbonate, anhydrous sodium acetate, and sodium sulfate, the manganese source is manganese dioxide or manganese acetate tetrahydrate, and the iron source is ferric oxide.

3. The method for preparing a molten salt of a sodium ferromanganate layered positive electrode material according to claim 1, characterized in that: In the step 2, the rotation speed of the planetary ball mill for ball milling is 400-600 rpm, and the ball milling time is 6-8 hours.

4. The method for preparing a molten salt of a sodium ferromanganate layered positive electrode material according to claim 1, characterized in that: In the step three, the pressing pressure is 10-12MPa, the high temperature sintering temperature is 900-1000°C, the starting temperature is room temperature, the temperature is increased by 3-5°C per minute, and the temperature is kept for 10-20 hours. After the insulation is completed, the sample is naturally cooled to room temperature with the furnace, and the heat treatment is carried out in air throughout the process.

5. The method for preparing a molten salt of a sodium ferromanganate layered positive electrode material according to claim 1, characterized in that: In the step 5, the annealing temperature is 500-700° C. and the time is 5-10 hours.

6. The method for preparing a molten salt of a sodium ferromanganate layered positive electrode material according to claim 1, characterized in that: In the step 4, an organic filter membrane is used for vacuum filtration, and deionized water is first used to filter repeatedly for 3-5 times to fully remove the residual potassium chloride molten salt, and then anhydrous ethanol is used to filter repeatedly for 3-5 times.

7. The method for preparing a molten salt of a sodium ferromanganate layered positive electrode material according to claim 1, characterized in that: In the steps 2 and 4, the temperature of the blast oven is 60-80° C., and the drying time is 10-12 hours.

8. A sodium ferromanganate layered positive electrode material obtained according to the molten salt preparation method of claim 1.

9. Application of the sodium ferromanganate sodium ion positive electrode material prepared by the molten salt preparation method according to claim 1 in the field of sodium ion batteries.

Citation Information

Patent Citations

  • O3-type nickel-iron-manganese-based sodium battery positive electrode material and preparation method thereof

    CN117936748A

  • Preparation method of long-circulation sodium ion battery positive electrode material and sodium ion battery

    CN116895744A

  • O3 type sodium ion positive electrode material and preparation method and application thereof

    CN117276521A

  • Method for preparing layered positive electrode material of sodium-ion battery at low temperature

    CN117720136A

  • Preparation method of layered oxide positive electrode material of sodium-ion battery

    CN118684282A

Cited By

  • Single-crystal positive electrode material for sodium-ion battery and preparation method and application of single-crystal positive electrode material

    CN121123256A